Surgical Technologists' Live Experiences of Professionalization: A Phenomenological Study - Behzad Imani; Shima Bahrami jalal (Kerman University of Medical Sciences, 2022)
Background: The rapid advancement of science and new technologies has brought wide-range changes in all professions, leading to the emergence of new concepts, including professionalism. This study aimed to explain the concept of professionalism from the perspective of surgical technologists. Methods: The present study was a qualitative one with conventional content analysis. A total of 11 surgical technologists were selected using purposive sampling method based on data saturation. Data were then collected using in-depth interviews. Data analysis was performed using Graneheim and Lundman's approach. Results: In data analysis, three main themes including professional attitude, professional mastery, and holistic professional care as well as seven subthemes were extracted from the data. Conclusion: According to the findings, professionalism indicates the type of attitude of the operating room nurses towards the profession as well as the degree of their mastery in providing professional care to patients.